ANALISIS DINAMIKA PERUBAHAN DAN PREDIKSI TUTUPAN LAHAN DI KECAMATAN PETUNGKRIYONO - Ridho Aryan Santoso (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
Petungkriyono District, Pekalongan Regency, is a primary tropical forest area simultaneously designated as a Strategic Tourism Zone, horticultural agropolitan area, and landslide-prone zone under the Pekalongan Spatial Plan (RTRW) 2020–2040. This overlapping policy framework has created compounding pressures on land cover, culminating in a flash flood and landslide disaster in January 2025 that claimed 25 lives. This study aims to analyze land cover change dynamics in Petungkriyono District during the period 2018–2025 and to predict land cover conditions in 2030. The methodology employs Sentinel-2A satellite imagery classification using Maximum Likelihood Classification (MLC) to generate annual land cover maps, followed by predictive modeling through Cellular Automata–Markov Chain (CA-MC) implemented via the MOLUSCE plugin in QGIS, incorporating four driving variables: distance to roads, slope, elevation, and distance to rivers. Results indicate that forest land declined from 6,798 Ha (81.86%) in 2018 to 6,335 Ha (76.29%) in 2025, while built-up land increased by 61.58% and agricultural land expanded by 20.34% over the same period. The dominant conversion pathway was forest to horticultural farmland, totaling a cumulative 2,595 Ha. The predictive model, validated with an overall Kappa of 0.834 and 93.55% correctness, projects a further 550 Ha reduction in forest cover by 2030. The ANN component Kappa of 0.5972 indicates moderate model capacity; results are therefore better interpreted as an early warning scenario. This study recommends zonation-based tourism management, phased mitigation for settlements in hazard-prone areas, and agricultural intensification as alternatives to continued land expansion.